Anxiety And Eating Behavior In Adults: A Literature Review - Capelini, Isadora Helena Bento; Frassetto, Alessandra Zanette Ghisi; de Souza, Maria Cristina Gonçalves; Guimarães, Paula Rosane Vieira (Seven Editora, 2023)
Anxiety is described as a mental and psychic response of the human body to situations of fear or threat, being manifested through various symptoms such as tremors, shortness of breath, increased heartbeat, sweating, gastrointestinal changes, among others. The Anxiety Disorder directly affects the psychological state of the individual, and may intensify his emotions and, consequently, interfere with his eating behavior. Psychological changes such as anxiety and stress can induce the individual to behave in a restrictive, compulsive, compensatory, and/or purgative way. This behavior can cause excessive consumption of food, and this consequently influences the individual's nutritional status. The aim of this study was to investigate the relationship between anxiety and eating behavior in adults through a literature review. This is a narrative literature review based on articles and theses selected from sites such as Scielo, Google Scholar, CAPES and databases of the Federal Government of Brazil, as the Health Surveillance Agency (ANVISA) and the Ministry of Health. A total of 24 articles were selected, 7 about eating behavior, 7 about nutritional status, 7 about the prevalence of anxiety and binge eating, and 3 about foods that reduce anxiety symptoms. It was possible to observe that anxiety influences the individual's eating behavior. High levels of anxiety were observed in patients with binge eating disorder, which affects the individual's nutritional status. Among genders, females have higher levels of anxiety and binge eating. The population needs interventions that reduce anxiety levels. Food plays a role in the prevention and treatment of some diseases; the effects of a healthy eating pattern bring physical and mental benefits to the individual. The Nutritionist, through food can influence the reduction of anxiety symptoms, with foods that have a beneficial influence on the body and the performance of a multidisciplinary team is essential, in order to bring more effective results. DOI: https://doi.org/10.56238/colleinternhealthscienv1-105